Impacto da embolização arterial do leiomioma uterino no volume uterino, diâmetro do mioma dominante e na função ovariana - Bernardo, Andre [UNIFESP] (2011)
PURPOSE: To evaluate the impact of the mioma arterial embolization (EAM) by uterine volume, mioma diameter greater and in the ovarian function, was carried through before and after three months of the procedure, pelvic ultrasonography for the transvaginal way (USPTV) and dosages of FSH (follicle-stimulating hormone). METHODS: Thirty patients carrying of symptomatic leiomyomas had participated of the study that they had been submitted to the EAM after science and signature of the term of free and clarified assent, obeying the criteria of inclusion of the study. Examinations of USPTV for the same professional had been carried through, in the same device before and after three months of the EAM. The uterus volume was express in cm³ e mioma diameter greater in cm. Had been made dosages of FSH before and after three months of the EAM in the central laboratory of the Hospital São Paulo. The values had been quantified in UI/ml, analyzed and express for medium+/-shunting line standard. The data then had been submitted the statistics analysis for the test distribution free of Mann-Whitney. RESULTS: It had the exclusion of a patient due to lack of data after EAM. The average before EAM uterine volume was 402,4±165,9cm³, before-EAM mioma diameter greater 5,928±2,126cm. The observed result was after-EAM uterine volume was 258,9±118,6cm³ and after-EAM mioma diameter greater 4,607±1,858cm. The average of the dosage before-EAM FSH was 4,997 (±3,520) UI/ml and after-EAM FSH was 5,500 (±4,759) UI/ml with p=0,581*. In hormone dosages, 29 cases had been evaluated. One case, that is equivalent 3.4% of the total, attended a course with definitive increase of FSH. It had reduction of 35% of the uterus volume, of 22% in the size of the mioma diameter greater and the EAM did not modify the FSH values significantly after 3 months. CONCLUSION: The procedure causes reduction of the uterine volume and leiomyomas preserving the uterus and, does not provoke ovarian function alterations.